PENERAPAN LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK SELF INSTRUCTION UNTUK MENINGKATAN ADVERSITY QUOTIENT PADA SISWA UNDERACHIEVER - Susilawati Susilawati; R. Ika Mustika; Ecep Supriatna (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
One of the factors that influence achievement is the level of intelligence. From this background, this research formulates research objectives, namely to determine the implementation, teacher and student responses and the constraints experienced by students when implementing group guidance services with self-instruction techniques to increase adversity. quotient in underachiever students. The method used in this research is descriptive method with a qualitative approach. The subjects in this study were 32 underachiever students in class XI MIPA at SMA Negeri 1 Garut for the academic year 2019 - 2020. The results of the study were obtained group guidance services with self-instruction techniques can be used to improve adversity quotient for underachiever students in class XI MIPA SMA Negeri 1 Garut. The response of most underachiever students with low adversity quotient felt very happy with the implementation of group guidance services with self-instruction techniques and most of them became better and more knowledgeable about self-instruction technique group guidance services in increasing adversity quotient. The constraints faced by students are that not all students are motivated to take group guidance services with self-instruction techniques, because there are still some who don't, so that students still find it difficult to express their opinions in group discussions.Keywords: : Self Instruction Technique, underachiever students, Adversity quotient